Speech Recognition, And Chatbot: Innovation In Indonesian Language Learning For Generation Z In The Digital Era - Asrofi, Asrofi; Widodo, Joko; Zuhriah, Nurul; Eriyanti, Ribut Wahyu; Iswatiningsih, Daroe; Sunaryo, Hari (CV. Bimbingan Belajar Assyfa, 2025)
The development of digital technology and the unique characteristics of Generation Z have driven the need for innovation in Indonesian language learning, particularly to improve the speaking skills of junior high school students. Conventional learning methods are often ineffective in building student confidence, creativity, and active participation. This study aims to develop and test the effectiveness of synergy between theater, speech recognition technology, and chatbots as a more interactive and relevant learning innovation. Using a Research and Development (R&D) approach using the ADDIE model, this study collected data through observations, interviews, questionnaires, and a pilot test of the teaching module. The results showed significant improvements in students' speaking skills, including fluency, clarity, and argument structure. Students became more confident, creative, and engaged, thanks to the automatic feedback from the speech recognition technology and adaptive conversational practice provided by the chatbot. This innovative module also increases student motivation and engagement, supports the implementation of the Independent Curriculum, and the development of 21st-century skills. This synergy has proven effective and can be widely adopted to create more personalized learning that meets the demands of the digital age.